Does adoption of superior Murrah buffalo germplasm pay off? evidence from a causal impact study in Haryana, India - Gururaj, Makarabbi; Aiswarya, S.; Supriya, Chhotaray; Kumar, Sanjay (Frontiers in Genetics, 2026)
Buffaloes play a pivotal role in sustaining rural livelihoods, milk production, and nutritional security in South Asia, where genetic improvement remains a critical pathway to enhance productivity and profitability. Despite decades of breeding efforts, limited empirical evidence exists on the socio-economic impact of disseminating superior germplasm under structured progeny testing programs. This study employed a quasi-experimental design to evaluate the effects of the Central Institute for Research on Buffaloes (CIRB) Murrah superior germplasm disseminated under the Field Progeny Testing (FPT) program of the Network Project on Buffalo Improvement (NPBI) in Hisar district, Haryana, India. Treatment households were defined as adopters of CIRB superior germplasm, while non-adopters from comparable control villages, located approximately 40–50 km away to avoid spill-over, served as the control group. A total of 200 respondents (100 treatment and 100 control) were selected through a combination of purposive and random sampling. Data were collected using key informant interviews, focus group discussions, and structured household surveys, and analysed using doubly robust econometric approaches, including Inverse Probability Weighted Regression Adjustment (IPWRA), Propensity Score Matching (PSM), and Coarsened Exact Matching (CEM). Our findings suggest that calf birth weight, age at first calving, dry period, average daily milk yield, and cost of artificial insemination significantly influence the net income of buffalo-rearing households. Adoption of CIRB Murrah superior germplasm through the FPT program led to a significant higher annual net income by $405.94 per buffalo, average daily milk yield by 1.53 kg, and calf birth weight by 5.53 kg, while reducing Age at First Calving (AFC) by 2.94 months and shortening dry periods by 1.83 months in comparison with control group. The study further indicates that efficient reproductive management and affordable AI services are critical for realizing the full economic potential of buffalo herds. Consequently, the findings emphasize that targeted dissemination of superior germplasm combined with technical guidance on feeding, breeding, and health management is essential for enhancing productivity and profitability in dairy systems.